Revitalisasi Revitalisasi Kampung Dolanan Sebagai Upaya Pelestarian Permainan Tradisional di Desa Sanankerto Kecamatan Turen Kabupaten Malang - Melani Albar; Mat Syafi'ih; Rofiqoh Firdausi (Jurnal Pengabdian Masyarakat: Tipis Wiring, 2024)
Dolanan village generally means a place where children play. With the existence of this dolanan village, it becomes a place to preserve and teach traditional playing culture where currently traditional games have been eroded by the development of more modern times. Dolanan Village in Sanankerto Village, Turen District, is a thematic village that needs attention from stakeholders, where Sanankerto Village has been named as one of the National Tourism Villages in Tuiren District, Malang Regency. However, of course, in realizing Dolanan village as an effort to preserve traditional game culture, it is necessary to emphasize collaboration between stakeholders so that sustainability in the cultural realm related to traditional games can be achieved. In addition, it is hoped that wider benefits can be obtained by the community, whether directly or indirectly involved, positive impacts are expected on various aspects such as economic, social, cultural, educational, etc. Keywords: Revitalization; Kampung Dolanan; Traditional game